ANALYSIS AND APPLICATION OF THREE-DIMENSIONAL CRACK GROWTH BASED ON FRANC3D - AI ShuMin; YU Ming; CHENG XiaoMing; WANG JianFang (Jixie qiangdu)
The basic theory and solution flow of Franc3D were firstly focused,then elliptical embedded crack and semielliptical surface crack were employed to verify the stress intensive factor calculation accuracy from Franc3D and typical sheet problem was utilized to validate crack growth analysis reliability. Three-dimensional crack growth analysis of a blisk was also included proving that present research could benefit structural crack propagation analysis and damage tolerance design in engineering application.